Problems: Ted Eisenberg, Section Editor
Problems: Ted Eisenberg, Section Editor
Problems: Ted Eisenberg, Section Editor
*********************************************************
This section of the Journal offers readers an opportunity to exchange interesting mathematical
problems and solutions. Please send them to Ted Eisenberg, Department of Mathematics,
Ben-Gurion University, Beer-Sheva, Israel or fax to: 972-86-477-648. Questions concerning
proposals and/or solutions can be sent e-mail to <eisenbt@013.net>. Solutions to previously
stated problems can be seen at <http://www.ssma.org/publications>.
————————————————————–
(3) ax3 + by 3 = 17
ax4 + by 4 = 33.
(4)
5504: Proposed by Ovidiu Furdui and Alina Sı̂ntămărian both at the Technical
University of Cluj-Napoca, Cluj-Napoca, Romania
Let n ≥ 0 be an integer. Calculate
1
xn
Z
1 dx,
0 x
where bxc denotes the integer part of x.
Solutions
2
For the problem at hand, the semiperimeter s of our triangle is
3 + x + (x + 1)
s= =x+2
2
and Heron’s Formula for the area A yields
p
A = s (s − 3) (s − x) (s − x − 1)
p
= (x + 2) (x − 1) (2) (1)
p
= 2 (x2 + x − 2).
A2 = 2 x2 + x − 2 = 4k 2
or
x2 + x − 2 − 2k 2 = 0. (4)
By the Quadratic Formula, the positive solution of (4) is
p
−1 + 1 + 8 (k 2 + 1)
x=
√ 2
−1 + 8k 2 + 9
= .
2
For x to be a positive integer, we will need
8k 2 + 9 = m2
or
m2 − 8k 2 = 9
for some odd positive integer m. However, table (3) gives us six solutions to use. In each
case, √
−1 + 8k 2 + 9 m−1
x= = and A = 2k.
2 2
The solution m1 = 9 and k1 = 3 yields x = 4, which is ruled out in the statement of the
problem. The other five entries in the table provide five plausible values of x for which
A is a positive integer. These values are listed in our final table:
n mn kn x A
2 51 18 25 36
3 297 105 148 210
4 1, 731 612 865 1, 224
5 10, 089 3, 567 5, 044 7, 134
6 58, 803 20, 790 29, 401 41, 580
3
Let p and S be the semi perimeter and the area of such a triangle respectively. Then
2p = 3 + x + x + 1 = 2x + 4 and, by Heron’s formula
p √
S = p(p − 3)(p − x)(p − (x + 1)) = 2x2 + 2x − 4 must be an integer.
It can be easily verified that for each of the five values of x ∈ {25, 148, 865, 5044, 29401}
one obtains triangles that have areas of 36, 210, 1224, 7134, 41580, respectively.
x1 25
More generally, if = , then the recurrence given by
S1 36
xn+1 3 2 xn 1 xn+1
= + for any integer n ≥ 1, gives a pair
Sn+1 4 3 Sn 2 Sn+1
where xn+1 is the length of a triangle with integer length sides (3, xn+1 , xn+1 + 1)
and Sn+1 is the integer area of that triangle.
Solution 3 by Julio Cesar Mohnsam and Luiz Lemos Junior, both at IFSUL
Campus Pelotas-RS, Brazil
3+x+x+1
Let p be the semi-perimeter p = =x+2
2
The area
p by Heron is given by: p
A = p(p − 3)(p − x)(p − x − 1) = (x + 2)(x − 1)(2)(1)
Then (x + 2)(x − 1)(2) must be a square, that is, 2x2 + 2x − 4 = y 2 , follow that:
2x2 + 2x − y 2 − 4 = 0 (1)
Multiplying (1) by 8 we have:
X 2 − 8Y 2 − 36 = 0 (4)
(4) is a diophantine equation of the form ax2 − by 2 + c = 0 in the case of c = −1 we have
the particular case of the equation of Pell x2 − Dy 2 = 1. If (a, b)|c, the equation has a
solution. Let’s solve (4) using the method Florentin Smarandache [1].
We consider the equation
aX 2 − bY 2 + c = 0 (5)
and
aα2 − bβ 2 = a (6)
We set the matrix A from (6) as follows:
b
α0 a β0
A=
β0 α0
where (α0 , β0 ) are initial solutions of (6).
4
Now let (X0 , Y0 ) are initial solutions of (5), then the general solutions of (5) are given by
the following recurrence relation:
Xn n X0
=A
Yn Y0
Thus, by solving (4) we have to first assemble matrix A from X 2 − 8Y 2 = 1, note that
this Pell equation has initial solution (3, 1), so we have:
3 8
A=
1 3
But (4) has initial solution (6, 0). So we have to:
X1 3 8 6 18
= =
Y1 1 3 0 6
Like 18 = X1 = 4x1 + 2 → x1 = 4 but we have to find x > 4.
Thus we calculate A2 , such that:
2
X2 3 8 6 17 48 6 102
= = =
Y2 1 3 0 6 17 0 36
As 102 = X2 = 4x2 + 2 → x2 = 25 and the lengths of the first triangle are (3, 25, 26). To
find the other values of x we will diagonalize the matrix A. We know that
An = P Dn P − 1.
−1 λ1 0
A = P DP = P P −1
0 λ2
√ √
Eigenvalues λ1 = 3+ 2√ 3 and λ2 = 3 − 3√
2
2 3 −2 3
Eigenvectors ~v1 = and ~v2 =
1 1
Therefore x = {25, 148, 565, 5044, 29401}
[1] Smarandache F. “Un metodo de resolucion de la ecuacion diofantica. Gazeta
Matematica, Serie 2, Vol. 1, Nr. 2, 1988. Madrid. p. 151-157.
5
Thus there are infinitely many integers x which satisfy the requirements of the problem,
given by the terms xn (with n ≥ 2) of the sequence
x0 = 1, x1 = 4, and xn+2 = 6xn+1 − xn + 2 for n ≥ 0.
In particular, the next five values of x after 4 are 25, 148, 865, 5044, and 29401.
√
Addenda.√(i) We may also describe the above sequences by letting γ = 3 + 2 2 and
δ = 3 − 2 2. Then an = (γ n + δ n )/2 for each n ≥ 0, which implies that
xn = (3γ n + 3δ n − 2)/4.
(ii) We further note that the ratios an /bn for n ≥ 1 occur as every √
other term in the
sequence of converging to the continued fraction representation of 2.
Comments by Editor : Ioannis D. Sfikas of Athens Greece started his solution off
with some nomenclature and bit of history about the problem.
“A triangle whose sides and area are rational numbers is called a rational triangle. If the
rational triangle is right-angled, it is called a right-angled rational triangle or a rational
Pythagorean triangle or a numerical right triangle. If the sides of a rational triangle is of
integer length, it is called an integer triangle. If further these sides have no common
factor greater than unity, the triangle is called a primitive integer triangle. If the integer
triangle is right-angled, it is called a Pythagorean triangle. A Heronian triangle (named
after Heron of Alexandria) is an integer triangle with the additional property that its
area is also an integer. A Heronian triangle is called primitive Heronian triangle if sides
have no common factor greater than unity. In the 7th century, the Indian mathematician
Brahmagupta studied the special case of triangles with consecutive integer sides.”
Kenneth Korbin, the proposer of this problem √ stated that triangles sides with
lengths (3, x, x + 1) with x ≥ 4 have an area of 2x2 + 2x − 4, and are associated with
the sequences of (25, 148, 865, 5044, 29401, . . . , xN , . . .) that satisfies the recursion of
xN +1 = 6xN − xN −1 + 2.
David Stone and John Hawkins of Southern Georgia University asked in their
solution, why the values of x ≥ 4? Why not x > 0? They then stated that: If
They then asked: What about those Heronian triangles of the form (3, x, x + 2), where x
is an integer. Applying Heron’s Formula they obtained that 16A2 = 20x2 + 40x − 25 and
stated that there are no integer solutions to this for x ≥ 1 because the left-and side is
even while the right hand side is odd.
They then looked at triangles of the form (3, x, x + 3) and stated that the only triangle
of this form is degenerate. Moreover, no triangle of the form (3, x, x + d) can exist for
d > 3.
They continued on with the following:
“Thus the problem poser selected the one form that does admit solutions. Still to be
6
investigated: finding the Heronian triangles of the form (4, x, x + 1), and those of the
form (4, x, x + 2), etc.”
Their solution ended with the statement: “There are no Heronian triangles of the form
(n, x, x + d) for positive integers n and d having opposite parity.”
Solution 2.
Since, for a fixed natural number n, (tan x)n is an increasing positive function for
x ∈ [0, 90◦ ), we have
(tan 3◦ )n (tan 3◦ )n
≥ ,
(tan 2◦ )n + (tan 1◦ )n (tan 4◦ )n + (tan 5◦ )n
and
◦
(tan 4 ) n (tan 4◦ )n
≥ ,
(tan 3◦ )n + (tan 2◦ )n (tan 3◦ )n + (tan 5◦ )n
7
so that
X (tan 3◦ )n (tan 5◦ )n (tan 4◦ )n (tan 3◦ )n
≥ + + .
(tan 2◦ )n + (tan 1◦ )n (tan 4◦ )n + (tan 3◦ )n (tan 3◦ )n + (tan 5◦ )n (tan 4◦ )n + (tan 5◦ )n
cyclic
Setting a = (tan 3◦ )n , b = (tan 4◦ )n , and c = (tan 5◦ )n , we see that the right-hand side of
the last inequality has the form
a b c
+ + ,
b+c c+a a+b
for a, b, c > 0, which is greater than or equal to 3/2 by Nesbitt’s inequality. Equality
holds if and only if n = 0 (assuming that 0 is considered a natural number).
1 1 1 3
+ + ≥
tan 4◦ tan 3◦ tan 3◦ tan 2◦ tan 2◦ tan 1◦ 2
◦
+ ◦ ◦
+ ◦ ◦
+ ◦
tan 5 tan 5 tan 4 tan 4 tan 3 tan 3
Substituting the values from steps 1-5 and performing the indicated divisions we define:
1 1 1
f (n) = + + .
(.799267114)n + (.599023652) n n
(.794551256) + (.499433116) n (.66632797) + (.333062483)n
n
We note that f (n) is an increasing function of n since the denominators clearly decrease
as n increases.
3
Finally we note that f (1) = .715158838 + 1.248899272 + 1.000609919 = 2.964668029 > .
2
Then the equality holds for all n since f (n) is an increasing function.
(bx + ax ) cx ln c − cx (ax ln a + bx ln b)
f 0 (x) =
(bx + ax )2
8
(bx + ax ) ln c − (ax ln a + bx ln b)
= cx
(bx + ax )2
bx (ln c − ln b) + ax (ln c − ln a)
= cx .
(bx + ax )2
The ln function is increasing, so ln c > ln b and ln c > ln a; thus we see that the derivative
1
is positive. Hence the function f is increasing, so = f(0) ≤ f (x) for x ≥ 0. Because
2
1
the derivative is strictly positive, the function f actually grows: so f (x) > for x > 0.
2
To verify the inequality of the problem, we note that the tangent function is increasing,
so in each summand the tangent term in the numerator is larger that each tangent term
in the denominator. Hence we can apply the lemma to each of the three summands,
3
forcing the sum ≥ . Note that equality holds if and only if n = 0.
2
Comment: We can apply the lemma to obtain some ugly inequalities which are clearly
true:
3n 4n 5n (n + 2)n n
+ + + · · · + ≥ , and
1n + 2n 2n + 3n 3n + 4n nn + (n + 1)n 2
[(n + 2)!]n 1
≥ .
[n!]n + [(n + 1)!]n 2
Also solved by Arkady Alt, San Jose, CA (two solutions); Paul M. Harms,
North Newton, KS; Kee-Wai Lau, Hong Kong, China; Paolo Perfetti,
Department of Mathematics, University of Tor Vergata, Rome, Italy; Angel
Plaza, University of Las Palmas de Gran Canaria, Spain; Ioannis D. Sfikas,
National and Kapodistrian University of Athens, Greece; Albert Stadler,
Herrliberg, Switzerland, and the proposers
9
The AHM yields
4
a+b≥ 1 1 ⇐⇒ (a + b)2 ≥ 4ab
a + b
and then
sin x 2ab tan x 4ab sin x 2ab tan x
(a + b) · + · ≥ · + ·
x a+b x a+b x a+b x
Thus we prove
4ab 2ab 6ab
· sin x + · tan x − x≥0
a+b a+b a+b
This is equivalent to
.
f (x) = 4 sin x + 2 tan x − 6x ≥ 0
2
f 0 (x) = 4 cos x + −6
cos2 x
00 4 sin x 4
f (x) = −4 sin x + = 4 sin x −1 >0
cos3 x cos3 x
via cos x ∈ (0, 1) for 0 < x < π/2. Since f 0 (0) = f (0) = 0 we get f (x) ≥ 0.
Proof of (ii).
Let √
f (x) = a · tan x + b · sin x − 2x ab,f (0) = 0
√ √ √
r
0 a a ab cos x
f (x) = + b cos x − 2 ab ≥ + b cos x − 2 ab ≥ 2 − 2 ab = 0
cos2 x cos x cos x
and this concludes the proof.
10
π x3 x3
It is well known that for x ∈ 0, , we have sin x − and tan x ≥ x + . Since
2 6 3
4ab + (a − b)2 4ab
a+b= ≥ , so the left side of (i) is greater than or equal to
a+b a+b
x2 x2
2ab 2 sin x + tan x 2ab 6ab
≥ 2 1− + 1+ = ,
a+b x a+b 6 3 a+b
as required.
π x2 x4
It is also well known that for x ∈ 0, , cos x ≤ 1 − + , so that
2 2 24
2
x3 x2 x4 x4 (12 − x2 )
sin2 x = x2 cos x ≥ x − − x2 1 − + = ≥ 0.
6 2 24 72
Hence,
r
p √ sin2 x √
a · tan x + b · sin x ≥ 2 (a tan x)(b sin x) = 2 abx ≥ 2 abx
x2 cos x
and (ii) holds.
5484: Proposed by Mohsen Soltanifar, Dalla Lana School of Public Health, University
of Toronto, Canada
Let X1 , X2 be two continuous positive valued random variables on the real line with
corresponding mean, median, and mode x1 , x e1 , x
b1 and x2 , x
e2 , x
b2 respectively. Assume
for their associated CDFs, (Cumulative Distribution Functions) we have
11
Let p2 (x) = 36x, if 0 ≤ x ≤ 1/6, p2 (x) = 12 − 36x, if 1/6 ≤ x ≤ 1/3, p2 (x) = 0, if x ≤ 0
or x ≥ 1/3.
Z 1 Z 1
p1 (x) and p2 (x) are probability density functions since p1 (x)dx = p2 (x)dx = 1.
0 0
Z x Z x
Obviously, FX 1 (x) = p1 (t)dt ≤ p2 (t)dt = FX2 (x), however xf1 = 3, xf2 = 6.
0 0
Let X be a continuous random variable on the real line with CDF FX (t) and mean x. It
Z ∞ Z 0
is known that x = (1 − FX (t))dt − FX (t)dt, provided at least one of the two
0 −∞ Z 0 Z 0
integrals is finite. Since X1 , X2 are positive, so FX1 (t)dt = FX2 (t)dt = 0 and
−∞ −∞
(i) follows from the fact that
Z ∞ Z ∞
x2 − x1 = ((1 − FX2 (t)) − (1 − FX1 (t))) dt = (FX1 (t) − FX2 (t)) dt ≤ 0.
0 0
Next we consider the medians, assuming that x e is the least number a satisfying
1
FX (a) = . Suppose, on the contrary, that x f2 > xf1 . Since FX (t) is a non-decreasing
2
x
f1 + x
f2
function and x1 < <x
f2 , we have
2
1 x
f1 + x
f2 x
f1 + xf2 1
FX2 (f
x2 ) = > FX2 ≥ FX1 ≥ FX1 (fx1 ) = ,
2 2 2 2
We now show that (iii) does not necessarily hold. Define the probability density
functions fX1 (t) and fX2 (t) of X1 and X2 as follows:
x ≤ 0,
0
x ≤ 0,
0
x
≤ ≤
0 x 4,
16
2x
fX1 (t) = and fX2 (t) = 0 ≤ x ≤ 5,
8−x 25
4 ≤ x ≤ 8,
16
0 x ≥ 5.
0 x≥8
Then
12
x ≤ 0,
0
0 x ≤ 0,
x2
0 ≤ x ≤ 4,
32
2
x
FX1 (t) = and FX2 (t) = 0 ≤ x ≤ 5,
−x2 + 16x − 32
25
4 ≤ x ≤ 8,
32
1 x ≥ 5.
1 x≥8
It is easy to check that FX1 (t) ≤ FX 2 (t) for t > 0, but x
f1 = 4 < 5 = x
f2 .
This completes the solution.
(4x + 2y + 1)−3 ≥ 3.
Y X
(2x + 3y + z + 1)
cyclic cyclic
13
After expanding the inequality reduces to
2(x3 +y 3 +z 3 )+x2 +y 2 +z 2 +3(xy 2 +yz 2 +zx2 ) ≥ 3(x2 y +y 2 z +z 2 x)+xy +yz +zx+6xyz.
Also solved by Arkady Alt, San Jose, CA; Kee-Wai Lau, Hong Kong, China;
Paolo Perfetti, Department of Mathematics, Tor Vergata University, Rome,
Italy; Kevin Soto Palacios, Huarmey, Perú; Ioannis D. Sfikas, National and
Kapodistrian University of Athens, Greece; Albert Stadler, Herrliberg,
Switzerland, and the proposer.
14
Clearly xn increases and xn ≥ 1.
p p p−3
X xn x1 x2 X xn 3 X xn+3
= + + = + =
2n 2 4 2n 4 2n+3
n=1 n=3 n=0
p−3 p−3
3 X xn+2 + xn+1 + xn +
X n
= + 2n+3 2n+3 2n+3 n+3
=
4 2
n=0 | {z } | {z } | {z } n=0
I1 I2 I3
p−1 p−2 p−3 p−3
3 X xn X xn X xn X n
= + + + + =
4 2n+1 2n+2 2n+3 2n+3
n=2 n=1 n=1 n=0
| {z } | {z } | {z }
I1 I2 I3
p p
3 1 X xn xp X xn xp−1 xp
= +− + n+1
− p+1 + n+2
− p+1 − p+2 +
4 4 2 2 2 2 2
n=1
| {z } n=1
| {z }
I1 I2
p p−3
X xn xp−2 xp−1 xp n X
+ n+3
− p+1 − p+2 − p+3 + n+3
2 2 2 2 2
|n=1 {z } n=0
| {z }
I3 →1/4 as p→∞
It follows
p
1 X xn 1 h xp xp−1 xp xp−2 xp−1 i 1
= − p+1 + p+1 + p+2 + p+1 + p+2 +
8 2n 2 2 2 2 2 2 4
n=1
Now we prove the
Lemma xk /2k → 0.
Proof of the Lemma
First step: the sequence xk /2k in monotonic not increasing.
xk+3 xk+2 + xk+1 + xk + k xk+2 xk+1 + xk + k xk+2
k+3
= k+3
≤ k+2 ⇐⇒ k+3
≤ k+3
2 2 2 2 2
that is
x(k−1)+2 + x(k−1)+1 + (k − 1) + 1 ≤ x(k−1)+3
and this is implied by
via xk−1 ≥ 1. The monotonicity of the sequence means that the limit L of xk /2k does
exist and moreover 0 ≤ L < +∞. If L = 0 the proof is concluded yielding
p ∞
1 X xn 3 X xn
lim n
= ⇐⇒ =6
p→∞ 8 2 4 2n
n=1 n=1
1 1
L = L + L =⇒ L = 0
2 4
17
an+3 − an+2 − an+1 − an = 0, n ∈ N ∪ {0} . Thus, an = tn+1 , n ∈ N ∪ {0} and, therefore,
n 1
tn+1 xn = s (x) =
P
. In,
k=0 1 − x − x2 − x3
∞ t 1 P ∞ tn 1 1
P n
particular, n
= n−1−
= s =
n=1 2 2 n=1 2 2 2
1 1
· 2 3 = 4.
2 1 1 1
1− − −
2 2 2
∞ x ∞ t ∞ t ∞ t ∞ n
P n P n P n+1 P n+2 P
Then, n
= n
− n+1
+2 n+2
− n+1
=
n=1 2 n=1 2 n=1 2 n=1 2 n=1 2
∞ t ∞ t ∞ n
n n ∞ tn − 1
P P P
n
− n
+ 2 n=3 n =
n=1 2 n=2 2 2 2 n=1 2n
∞ t ∞ t
t1 P n 1 1 P n t1 t2 1 1 1
+2 − ·2=− +2 −2 + =− +2·4−2 + = 6.
21 n=3 2
n 2 2 n=1 2
n 21 22 2 2 4
Also solved by Kee-Wai Lau, Hong Kong, China; Ioannis D. Sfikas, National
and Kapodistrian University of Athens, Greece; Albert Stadler (two
solutions), Herrliberg, Switzerland; David Stone and John Hawkins,
Southern Georgia University, Statesboro, GA, and the proposer.
M ea − Culpa
18
Arkady Alt of San Jose, CA should have been credited with having solved 5477, and
5478.
Dionne Bailey, Elsie Campbell, Charles Diminnie, and Trey Smith, all of
Angelo State University in San Angelo, TX should have been credited with
having solved 5475.
Paul M. Harms, of North Newton, KS should have been credited for having solved
5476.
Anna Valkova Tomova of Varna, Bulgaria should have been credited with having
solved 5475 and 5477.
Mea Culpa.
19